A127 ENDOSCOPIC MUCOSAL RESECTION FOR DYSPLASTIC AND NEOPLASTIC BARRETT'S ESOPHAGUS: FINDINGS FROM A FOREGUT NEOPLASIA MULTIDISCIPLINARY DATABASE. (21st February 2022) - Wilson, H A; Blakely, P; Dang, J; Sun, W; McLean, R; Karmali, S; Wong, C
Abstract: Background: Previously, Barrett's esophagus with high grade dysplasia (HGD) or neoplasia was treated with esophagectomy, which is associated with a high postoperative morbidity and mortality rate. Recent guidelines support the use of endoscopic mucosal resection (EMR) for T1a esophageal adenocarcinoma (EAC) and potentially T1b EAC; however, data on long term outcomes of endoscopic treatment is lacking. We created a combined prospective and retrospective multidisciplinary database to monitor outcomes of patients with Barrett's esophagus undergoing endoscopic treatment. Aims: Our primary aim was to compare outcomes of EMR and esophagectomy in patients presenting with BE and HGD, and/or early EAC. Methods: A collaboration of gastroenterologists, general surgeons and thoracic surgeons from the University of Alberta, Edmonton, Alberta, provided input on the development of the database. All patients referred to the Northern Alberta Endoscopic Ablation Program from 2009–2021 who received at least one endoscopic treatment were included. A sub-analysis of all patients with pathologic confirmation of HGD, and/or early EAC was conducted to compare outcomes of EMR and esophagectomy. Results: A total of 212 patients have been entered into the database. The most common findings were HGD, low grade dysplasia (LGD), and adenocarcinoma, respectively. All patients (n=48) who had at least LGD reached complete eradication of dysplasia (CE-D) and 95.8% reached complete eradication of intestinal metaplasia (CE-IM). Of those patients that reached CE-D, 8.3% developed recurrence of dysplasia (n=4). In the sub-analysis, 74 patients (76.3%) received endoscopic therapy while 23 patients (23.7%) received endoscopic therapy then ultimately an esophagectomy. There were significantly more T1b lesions in the esophagectomy group compared to the EMR group ( p <0.0001). Of all the patients in the EMR group, only 5.4% (n=4) had treatment related complications. Of patients receiving an esophagectomy, 60.9% (n=14) experienced treatment related complications. The mean length of stay for patients in the EMR group was 1.03 +/- 0.2 days, compared to 16.5 +/- 11.8 days for esophagectomy ( p <0.0001). Conclusions: EMR provides definitive and durable treatment for BE lesions classified as T1b or less severe, with fewer complications and a shorter length of hospital stay than esophagectomy. Funding Agencies: Alberta Innovates Health Solutions